Evaluasi Penerapan Rekam Medis Elektronik dengan Pendekatan Technology Acceptance Model di Rumah Sakit X di Kota Surabaya - Intansari Intansari; Martya Rahmaniati; Dian Fajar Hapsari (Politeknik Negeri Jember, 2023)
Electronic medical records have an important in the provision of health services in hospitals, electronic medical records are a source of health data and information that can be used in assessing the quality of health services. Hospital X has implemented the use of electronic medical records since 2020 but has never conducted an evaluation of the implementation of electronic medical records, so need a formative evaluation to see the quality of electronic medical records using the Technology Acceptance Model, assessing a system based on the ease of use. use) and perceived usefulness (usefulness) which can affect the use of the system (attitude toward using) and applying the system on an ongoing basis (actual usage). This study uses a quantitative approach by using bivariate correlation test analysis to be able to assess the relationship between the variables studied. The results showed that there was a significant positive relationship (p-value 0.001, r = 0.717) between the belief that EMR can be used easily (perceived ease of use) and benefits in performance and performance productivity (perceived usefulness). p-value 0.001, r = 0.747) between EMR variables can provide benefits in terms of performance and performance productivity (perceived usefulness) and attitude toward using EMR (Attitude toward using). The belief that EMR can be used easily (perceived ease of use) has a positive and significant effect on attitudes towards using EMR (Attitude toward using) with a p-value of 0.001, r = 0.7, and a significant relationship with a p-value of 0.001, r = 0.717 between the belief that the attitude towards using EMR (Attitude toward using) and significant towards the actual use of EMR (actual usage)